Evaluation of HIV, STI and CD4 results among voluntary attendees at the HIV/AIDS program of Mexico City - Luis Alfredo Juárez-Figueroa; Felipe Javier Uribe-Salas; Andrea González-Rodríguez; Patricia Iracheta-Hernández; Verónica Ruiz-González; Yazmín Medina-Islas (Instituto Nacional de Salud Pública, 2017)
Objective. To describe results of HIV, sexually transmitted diseases (STI) and CD4 counts at the HIV-specialized Condesa Clinic (CC) in Mexico City. Materials and methods. Individuals who requested voluntary counseling and testing at CC were studied. We identified antibodies against HIV, syphilis, hepatitis C, and hepatitis B HBsAg. CD4 cell counts and viral load of HIV positive individuals were also obtained. Late HIV infection diagnosis was established if CD4 counts were lower than 200 cells/μL. Results. Global seroprevalence of HIV, syphilis, HBsAg, and anti HCV markers was of 20.1, 6, 1 and 1, respectively. Men displayed higher seroprevalence of infection markers than women. Among men, HIV infection was related to age and with all STI markers. Late HIV diagnosis was 31.8%. The risk of late HIV diagnosis was higher among women and it increased as age increased. Conclusions. Differences between genders regarding HIV and STIs prevalence as well as risk factors for HIV infection and late HIV diagnosis were observed.